The rebranding of the Lima Cathedral Museum - Rodríguez-Calmet, María Fernanda (2024)
In recent years, the Cathedral Museum of Lima has implemented brand rebranding as a new communication strategy. The aim of this study is to analyze how the rebranding of the Lima Cathedral Museum contributes to the formation of brand bonds. This study is situated in an interpretative paradigm. Fifteen semi-structured interviews were conducted with university students in the last cycles of the Hotel and Tourism career. Acceptance and positive attitude towards rebranding is evidenced, promoting, among them, their experience. It is concluded that the rebranding of the museum contributes to the formation of brand bonds. It is essential to continue promoting the tourist attraction so that they feel part of the Catholic community and, in turn, Peruvian and foreign visitors feel identified with Peruvian culture through this museum.